Traditional knowledge in HIV/AIDS treatment and prevention program in northern Uganda. Issue 1 (1st January 2016) - Akena, Francis Adyanga
Abstract : Uganda's health care sector is choking with various challenges, such as poor physical infrastructure, inadequate professionals to run the few existing health centers, poor culture of adherence to professional ethical standards by some health care practitioners, shortages of medicines in most government hospitals/health centers, and corruption. Most of the challenges are more endemic in rural areas. It is on the above premise that this article discusses some of the challenges that health centers face in provision of care to the increasing number of HIV/AIDS patients in hard-to-reach rural communities in northern Uganda and the implications of such challenges on the economy. Uganda's success in the fight against HIV/AIDS in the early 1990s was globally applauded because of its aggressive grassroots behavioral change crusades aimed at reducing the number of sexual partners. The success inspired a wave of financial aid programs from the US government to fight the disease across the developing world. However, the success was short-lived as the rate of HIV/AIDS infection in Uganda is currently rising, with the health care system struggling to provide care for the ballooning number of patients. To contribute to the curtailing cases of new infections, this article discuses the integration of the traditional authority and knowledge system in the national HIV/AIDS care and prevention program along with the biomedical approach currently being used.